Design of GIS-Based Attendance Application at SMA Santika East Jakarta - Saputro, Mohammad Ikhsan; Pertiwi, Santhi; Suryatno, Agung; Setiadi, Dedi; Sopian, Abu; Rifqi, Agven Muharis; Agustino, Rano (Universitas Mohammad Husni Thamrin, 2025)
In the digital era and industry 4.0 like today, human resource management (HR) is important for schools. One important aspect in human resource management (HR) in a school is employee attendance. Currently, for employee attendance at SMA Santika East Jakarta, the fingerprint attendance system is still used, which has shortcomings, such as the possibility of misuse of number codes that can lead to falsification of attendance. This study aims to develop an attendance application based on the Geographic Information System (GIS) at SMA Santika East Jakarta to improve the accuracy and reliability of the employee attendance system. In the context of the digital era and industry 4.0, proper employee attendance management is crucial, especially when employees work outside the office. To overcome this problem, this study designs a GIS-based attendance application that is able to track employee locations in real-time when taking attendance, both in the school environment and outside the school. The research methodology involves observation, interviews, and literature studies to obtain relevant data. The development model used is a prototype, which includes needs analysis, design, code development, testing, and system support. The application is developed using the React Native framework and TypeScript programming language, and is integrated with the Odoo system via REST API. With this application, it is hoped that SMA Santika East Jakarta can reduce the risk of attendance falsification and improve human resource management, as well as increase operational efficiency and accuracy of employee attendance data.